2012
DOI: 10.1061/(asce)is.1943-555x.0000104
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Rail Opportunities around Metropolitan Regions: Madrid and London

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 20 publications
0
22
0
2
Order By: Relevance
“…The final example is that of Stratford International which was designed as a focus for urban regeneration. Its location has, however, been seen as too close to London St Pancras for international services to stop; it is only 7 min from St Pancras and the cost of the security and border control measures needed for international services in the UK would be prohibitive (see Garmendia et al, 2012, for a further discussion of the UK intermediate stations).…”
Section: International Hsr Services Border Regions and Intermediate mentioning
confidence: 99%
“…The final example is that of Stratford International which was designed as a focus for urban regeneration. Its location has, however, been seen as too close to London St Pancras for international services to stop; it is only 7 min from St Pancras and the cost of the security and border control measures needed for international services in the UK would be prohibitive (see Garmendia et al, 2012, for a further discussion of the UK intermediate stations).…”
Section: International Hsr Services Border Regions and Intermediate mentioning
confidence: 99%
“…Blum et al (1997) project the advent of corridor regions with integrated but dispersed labor and consumption markets. Sasaki et al (1997) have modeled the potential for spatial dispersion of economic activities among Japanese HSR station-cities, and Garmendia et al (2008), Garmendia, Ribalaygua, and Ureñ a (2012) and Garmendia, Romero, Ureñ a, Coronado, and Vickerman (2012) have hypothesized the integration of smaller cities into the metropolitan region, encouraging the development of polycentric urban forms. Button (1990) and Bruinsma and Rietveld (1993), on the other hand, have argued that increased inequality between locations will emerge as a result of the differential increase in accessibility.…”
Section: Regional Restructuringmentioning
confidence: 99%
“…In Germany, Ahlfeldt and Fedderson (2009) found that small cities along the KolnFrankfurt HSR corridor saw substantial increases in their Gross Domestic Product compared to other local towns. In Spain, small and intermediate cities on the HSR network, less than one hour (or up to 100 km) away from major metropolitan centers, accrued population growth, thanks to their integration to the larger metropolitan network, which also helped them attract new economic activities and housing investments (Garmendia, Ribalaygua, et al, 2012;Garmendia, Romero, et al, 2012; Ureñ a, Coronado, . For example, some workers now live in Ciudad Real, a small city 50 minutes from Madrid on the HSR line, and commute to Madrid for work (Garmendia et al, 2008).…”
Section: Differential Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have examined HSR's impacts on regional mediumsized cities in France and Spain (Bazin et al, 2006;Coronado et al, 2013;Ureña et al, 2009), on metropolitan cities including Madrid, Paris, and Rome (Delaplace et al, 2014;Garmendia et al, 2012;Pagliara et al, 2015), on the intermediate areas between major metropolitan areas (Vickerman, 2015), and on cities along HSR routes (Chen and Haynes, 2015;Wang et al, 2012;Wang et al, 2014b;Yan et al, 2014). Empirical studies conducted in China show that there has been an increase in accessibility of all cities and regions along HSR lines (Liu and Zhang, 2018).…”
Section: Introductionmentioning
confidence: 99%